2019
DOI: 10.1111/ggi.13797
|View full text |Cite
|
Sign up to set email alerts
|

Association between quality of life and sleep time among community‐dwelling stroke survivors: Findings from a nationally representative survey

Abstract: Results: Findings showed that stroke survivors' daily sleep time significantly varied by sex (P < 0.001), education (P = 0.006) and body mass index (P = 0.012). The EuroQOL-5 Dimension index (P < 0.001), and its dimensions of mobility (P = 0.011), usual activities (P < 0.001) and pain/discomfort (P = 0.005) showed significant differences among people with different sleep times. In the final model, after adjusting for covariates, respondents who slept ≤5 h had odds ratios of 1.82 (95% confidence interval 1.05-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…CHD patients with poor sleep quality should be taken into consideration when planning rehabilitation, and sleep time is the one of the key influencing factors to increasing quality of life 41 . A study showed that adults with chronic disease who slept <7 or > 8 h were more likely to report poor or fair health and frequent mental distress, and a U-shaped relationship between sleep duration and HRQoL was found 42 .…”
Section: Discussionmentioning
confidence: 99%
“…CHD patients with poor sleep quality should be taken into consideration when planning rehabilitation, and sleep time is the one of the key influencing factors to increasing quality of life 41 . A study showed that adults with chronic disease who slept <7 or > 8 h were more likely to report poor or fair health and frequent mental distress, and a U-shaped relationship between sleep duration and HRQoL was found 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality in patients with stroke should be considered when developing a rehabilitation plan. Moreover, sleep time is one of the key factors affecting quality of life improvement in patients with stroke; 6–8 h of sleep each day is recommended ( 64 ). However, evidence-based sleep recommendations, such as how to achieve 6–8 h of sleep per day, are needed from our health organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep quality in stroke patients should be taken into consideration when developing a rehabilitation plan. Moreover, sleep time is one of the key factors affecting quality of life improvement in stroke patients; 6-8 hours of sleep each day is recommended [49]. However, evidence-based sleep recommendations, such as how to achieve 6-8 hours of sleep per day, are needed by our health organizations.…”
Section: Discussionmentioning
confidence: 99%